2019
DOI: 10.1016/j.bbr.2018.12.005
|View full text |Cite
|
Sign up to set email alerts
|

22 kHz and 55 kHz ultrasonic vocalizations differentially influence neural and behavioral outcomes: Implications for modeling anxiety via auditory stimuli in the rat

Abstract: The communicative role of ultrasonic vocalizations (USVs) in rats is well established, with distinct USVs indicative of different affective states. USVs in the 22kHz range are typically emitted by adult rats when in anxiety-or fear-provoking situations (e.g. predator odor, social defeat), while 55kHz range USVs are typically emitted in appetitive situations (e.g., play, anticipation of reward). Previous work indicates that USVs (real-time and playback) can effectively communicate these affective states and inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 79 publications
(92 reference statements)
0
42
1
Order By: Relevance
“…Although these data suggest that Antide‐treated females might differ slightly from control females on some measures of responsiveness to novelty and fear‐inducing stimuli, this interpretation of the results was not supported by the underlying brain activity because no differences in c‐Fos labelling were evident between groups in the basolateral or medial amygdaloid nuclei. This lack of between‐group differences in c‐Fos measures was unexpected, given the sensitivity of the BLA to stressors, including aversive acoustic noises 89 . A potential explanation is that measures of immobilisation in the ASR task do not strongly reflect aversive responses, and future studies could benefit from employing startle amplitude measures instead.…”
Section: Discussionmentioning
confidence: 96%
“…Although these data suggest that Antide‐treated females might differ slightly from control females on some measures of responsiveness to novelty and fear‐inducing stimuli, this interpretation of the results was not supported by the underlying brain activity because no differences in c‐Fos labelling were evident between groups in the basolateral or medial amygdaloid nuclei. This lack of between‐group differences in c‐Fos measures was unexpected, given the sensitivity of the BLA to stressors, including aversive acoustic noises 89 . A potential explanation is that measures of immobilisation in the ASR task do not strongly reflect aversive responses, and future studies could benefit from employing startle amplitude measures instead.…”
Section: Discussionmentioning
confidence: 96%
“…We observed a striking difference in HR levels following 50-kHz versus 22-kHz playback, which lasted for almost 3 min ( Figure 4 F; Table S16 C). To the best of our knowledge, HR changes following rats' exposure to different USV were not described before despite some attempts ( Demaestri et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous playback studies have shown that presenting 50-kHz USV evoked various behaviors such as approach ( Wohr and Schwarting, 2007 ), positive responses to ambiguous cues ( Saito et al., 2016 ), reduction in fights ( Kisko et al., 2015a ), restoration of sexual activity in devocalized rats ( White and Barfield, 1989 ), and awakening from haloperidol-induced catalepsy ( Tonelli et al., 2018 ). Whereas, exposing rats to 22-kHz playback inhibited behavior ( Wohr and Schwarting, 2007 ), decreased locomotor activity during replay and immediately afterward ( Sales, 1991 ; Brudzynski and Chiu, 1995 ), and caused negative responses to ambiguous cues ( Saito et al., 2016 ), and anxiety-like behaviors ( Demaestri et al., 2019 ). Presentation of 50-kHz versus 22-kHz playback also resulted in activation of c-Fos in different brain areas ( Beckett et al., 1997 ; Sadananda et al., 2008 ; Ouda et al., 2016 ; Demaestri et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to previous work (Morozova et al, 2016), a comparison of a 3-week exposure to 50 dB-ultrasound of mixed frequencies (“white noise”) at the range of 16–20 kHz did not result in a depressive-like state. The exposure of single frequency US-wave, 22 kHz, leads to anxiety in the first 5 min after exposure (Demaestri et al, 2019), but continuous action of 22 kHz does not lead to behavioral changes, because of an adaptation to the unchangeable stress impact (da Oliveira et al, 2015).…”
Section: Introductionmentioning
confidence: 99%